1998
DOI: 10.1002/(sici)1096-9136(199805)15:5<393::aid-dia597>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate malabsorption following acarbose administration

Abstract: Carbohydrate absorption was assessed during acarbose administration to investigate the actions of this drug. In 7 healthy volunteers, breath hydrogen concentration was measured at 15-min intervals after administration of 6 g of lactulose, and continued until 4 h after the breath hydrogen level exceeded its pretreatment value by > or =10 ppm, then the amount of undigested carbohydrate was calculated following administration of various doses of acarbose and Ensure Liquid. Breath hydrogen data were also obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Adverse events, predominantly gastrointestinal symptoms, have frequently been reported in association with the administration of α-glucosidase inhibitors [23][24][25], though no side-effects resulted from the ingestion of jelly containing LEM in the current study. Kim et al reported that LEM suppressed postprandial glucose levels with few side-effects by α-glucosidase inhibitor [37].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Adverse events, predominantly gastrointestinal symptoms, have frequently been reported in association with the administration of α-glucosidase inhibitors [23][24][25], though no side-effects resulted from the ingestion of jelly containing LEM in the current study. Kim et al reported that LEM suppressed postprandial glucose levels with few side-effects by α-glucosidase inhibitor [37].…”
Section: Discussionmentioning
confidence: 69%
“…This indicates fermentation by intestinal microbes of carbohydrates that have escaped digestion in the small intestine and been transferred to the large intestine [21,22]. Hydrogen excretion was also observed when an α-glucosidase inhibitor, such as acarbose or miglitol, was administered to patients with available carbohydrates [23][24][25]. The available energy of nondigestible saccharides has been estimated at 2 kcal/g (8.36 kJ/g) according to the Health Promotion Act in Japan [26,27], which is lower than that of digestible carbohydrates (approximately 4 kcal, 16.72 kJ).…”
Section: Introductionmentioning
confidence: 96%
“…Reports about hydrogen excretion due to effects of acarbose are conflicting and depend on the type of carbohydrate in the test meal and the dose of acarbose. Sucrose‐ and dextrimaltose‐containing meals (33–100 g carbohydrates) resulted in hydrogen excretion with 50–200 mg of acarbose [30,31]. After ingestion of starchy meals (50 g carbohydrate) administered with 200 mg acarbose, hydrogen excretion was observed in one [32] but not in another study [33].…”
Section: Discussionmentioning
confidence: 99%
“…The alpha-glucosidase inhibitors (1) have no significant effect on total caloric intake, 22 (2) delay and decrease carbohydrate absorption, [23][24][25][26][27] (3) have not been directly evaluated for HGU, (4) have negligible effect on hepatic glucose output, 28,29 (5) reduce IR, 22,[30][31][32][33] (6) have variable effects on PGU, 22,28,30,[34][35][36][37][38] and (7) reduce plasma insulin concentrations. 22,[39][40][41][42][43][44][45] Studies meeting the review criteria for the target effects of the alpha-glucosidase inhibitors on the respective targets are summarized here.…”
Section: Alpha-glucosidase Inhibitors (Acarbose and Miglitol)mentioning
confidence: 99%
“…These findings are supported by Sobajima et al, where carbohydrate malabsorption, measured by hydrogen excretion following 2-month acarbose administration (50-100 mg three times daily) was estimated to be 31.6% of baseline. 25…”
Section: Caloric Intake and Intestinal Carbohydrate Absorptionmentioning
confidence: 99%